ACUTE FOVEALITIS. Issue Volume 16:Issues 2(2022) (March 2022) - Ledesma-Gil, Gerardo; Spaide, Richard F.
Abstract : Purpose: To describe the clinical, optical coherence tomography (OCT), and OCT angiography findings of a patient with a foveal disturbance from the acute phase to the resolution of the visual disturbances. Method: The patient had a comprehensive ophthalmic examination to include OCT and OCT angiography. Results: A 36-year-old man presented with decreased vision and distortion in the right eye. The right eye showed yellow-white punctate opacities in the central fovea. OCT showed numerous, well-defined, globular, aggregated, hyperreflective lesions that corresponded to the visible opacities along with a focal discontinuity of the outer retinal layers. Over 3 weeks, the patient's findings resolved, and the VA improved to 20/20. No abnormalities of the choriocapillaris flow were detected using OCT angiography. The lesion resolved without pigmentary change. Conclusion: The configuration of the hyperreflective deposits, the lack of pigmentary change, and the absence of OCT angiographic findings of flow problems in the choriocapillaris argue against a primary retinal pigment epithelial or choriocapillaris abnormality as the fundamental cause of the disease. The name acute fovealitis is suggested. Abstract : A patient presented with a condition suggesting acute retinal pigment epitheliitis but with features that differentiated it as a novel disease.